Pengaruh Pemberian Reward terhadap Kepercayaan Diri Anak Kelompok B di KB PAUD Mekar Sari Kundi - Marsella, Dwi (ICEJ : Islamic Childhood Education Journal, 2023)
This research was motivated by the lack of self-confidence in group B children at KB PAUD Mekar Sari Kundi. Self-confidence is a child’s basic capital for living everyday life. A child’s lack of self-confidence results in the child’s abilities not developing. Giving rewards is considered effective in increasing children’s self-confidence. This research aims to determine the effect of giving rewards on the self-confidence of group B children at KB PAUD Mekar Sari Kundi. This research uses a quantitative approach with experimental methods. The form of experiment used is Quasi Experimental Design with a Nonequivalent Control Group design. The research population was all group B children at KB PAUD Mekar Sari Kundi, totaling 40 people with the sampling technique using saturated sampling. The data collection techniques used are observation and documentation. The instruments in this research used observation sheets and assessment rubrics. Data validity uses construct validity. Data analysis techniques use statistical tests, namely normality tests, homogeneity tests, and hypothesis tests using the Independent Sample T-Test. Data analysis was carried out using SPSS version 22 software. The research results show that giving rewards can increase children’s self-confidence. This can be seen from the results of the Independent Sample T-Test which shows that the Sig. (2-tailed) is 0.000 where 0.000 < 0.05 with an error level of 5%, meaning H1 is accepted and H0 is rejected. So it can be concluded that there is a significant influence between giving rewards on the self-confidence of group B children at KB PAUD Mekar Sari Kundi.